PERANCANGAN APLIKASI ANALISIS DATA GROUP WHATSAPP - Ichsan; Munawarul Fattah; Dien Taufan Lessy (J-Innovation, 2020)
WhatsApp is the most popular chat application to communicate recently. Every smartphone user uses this application for sending text messages or video messages. Whatsapp claims that almost 55 billion messages are sent every day. The users spend an average of 300 minutes each day on Whatsapp, both on personal and group chats. One of the favorite features of WhatsApp that eases for mass chatting is group chat. Every WhatsApp user usually has at least five groups, including family, friends, offices, campuses, schools, communities, etc. Generally, the users do not know what happens in a WhatsApp group. To overcome this problem, the author designed a WhatsApp group data analysis application. To deal with, this study designed an application which can provide information about participationstatistics for WhatsApp group members, chat growth statistics in a WhatsApp group based on Month, Day and Hour. This applicationcan also find out often discussed content or words that are often mentioned in a WhatsApp group. Later the information will be presentedin a graph that is easy to understand